Tooth avulsion accidents due to urgent and emergency orotracheal intubation - Galvão, Anna Karyna F de Carvalho (Med Oral Patol Oral Cir Bucal, 2020)
BACKGROUND: Intubation is necessary during critical situations to reduce the risk of death. In Brazil, a need exists to determine the prevalence of tooth avulsions in emergency and urgent care. The objective of this study was to identify the causes of orotracheal intubation (OTI), the number of tooth avulsions, and the avulsed teeth that result from urgent and emergency intubation. MATERIAL AND METHODS: The sample consisted of 116 patients (total group) in intensive care units (ICUs) distributed across Group 1 (G1), which was composed of 71 patients from an urgent-care hospital, and Group 2 (G2), which was composed of 45 patients from an emergency hospital. Clinical examinations showed dental alveolus with signs of recent exodontia in the upper and lower anterior regions. Sociodemographic data and the reason for intubation were evaluated. The Shapiro-Wilk normality test, chi-square test, Fisher’s exact test, Mann-Whitney U test, and univariate logistic regression were performed with a significance level of 5%. RESULTS: The avulsion prevalence was 4.3%, with more cases receiving emergency intubation (n=4). All avulsions occurred in adults, and a significant difference (p=0.011) was observed with regard to the elderly. A 1-year reduction in age increased the chance of tooth avulsion during intubation by 1.09 times; being female increased the chance by 2.88 times. CONCLUSIONS: Pulmonary problems were the major causes of intubation, with the highest tooth avulsion prevalence observed during emergency intubation. The avulsed teeth were 11, 12, 13, 22, 32, and 33 across all cases. Key words:Tooth avulsion, tooth injuries, intubation, intensive care units, emergencies.